Visualisasi BigQuery Data Penjualan Toko Sembako Menggunakan Flatfrom Loker Studio - Zai, Feri Irawan; Riki Mustafa, Satria; Aini, Yulfita; Agung Setiawan; Maulana Dwi Sena (RJOCS (Riau Journal of Computer Science), 2024)
In today's digital era, grocery stores often use the Loker Studio and BigQuery platforms to analyze their sales data. In this study, we analyzed data on grocery store sales using this platform. First of all, we collect sales data from grocery stores that use the Loker Studio platform. This data includes information such as sales dates, products sold, prices, sales quantities, and more. We then transfer this data to BigQuery, a powerful database and data analytics platform. Next, we perform the data analysis steps using BigQuery. We use queries to analyze sales trends, find bestselling products, identify customer buying patterns, and evaluate grocery store performance over time. In addition, we also conduct customer segmentation analysis to understand their preferences and buying habits. The results of this data analysis provide valuable insights to grocery stores. By looking at sales trends, grocery stores can identify popular products and increase their stock. Analyzing customer purchasing patterns helps grocery stores optimize marketing strategies and target promotional campaigns more effectively. In addition, customer segmentation analysis enables grocery stores to provide more personalized and relevant services to their customers. By using the Loker Studio and BigQuery platforms, grocery stores can easily collect, manage and analyze their sales data. This helps them in taking better decisions and improving their business performance